INFLUENCES AND INSPIRATIONS IN CURRICULUM STUDIES RESEARCH AND TEACHING - Shields, Carmen; Podolski, Adam Garry; Guiney Yallop, John J., 1959- ([S.l.] : ROUTLEDGE, 2021)
This volume highlights lived experiences, personal inspirations and motivations, which have generated scholarship, and influenced the research and teaching of scholars in the field of curriculum studies. Offering contributions from new, established and experienced scholars, chapters foreground the ways in which the authors have been influenced by the mentorship and work of others, by personal challenges, and by the contexts in which they live and work. Chapters also illustrate how scholars have engaged in variety of methodological and autobiographical processes including narrative and poetic inquiry, autoethnography and visual arts research. Through a range of contributions, the book clarifies the origins and legacy of contemporary curriculum studies and in doing so, provides inspiration for beginning scholars and academics as they continue to find their voices in academic communities. Offering rich insight into the experiences and scholarship of a wide range of scholars, this volume will be of interest to students, scholars and researchers with an interest in curriculum studies, as well as educational research and methodologies more broadly.
Keywords: EDUCATION / Curricula; EDUCATION / Philosophy & Social Aspects; EDUCATION / Research; Education -- Curricula -- Research